potrzebuje na teraz, dam naj
a) 2a + (6b - 2a) + 3b =
b) 2x (x + 3) - 5 (x + x²) =
c) 7x - 3 (x + 2) + 10 - x =
d) 6 (x + a) - 5 (a + x) =
e) 10x + 2 b + 3a + 3b - 10a + 15x =
f) 7 x (7x - 7) - x (x + 7) + 7 (7 - x) =


Odpowiedź :

Odpowiedź:

a)   2a + ( 6b -2a ) +3b= 2a +6b -2a +3b= 9b

b)  2x ( x+3) -5 (x+x²)= 2x²+6x -5x -5x²= -3x²+x

c)  7x - 3 ( x+2) +10- x= 7x -3x -6 +10 -x= 3x +4

d)  6 ( x+a) -5 ( a+x)= 6x  +6a -5a  -5x= x +a

e)  10x +2b +3a +3b -10a +15x= 25x +5b-7a

f)   7x (7x-7) -x ( x+7) +7 (7-x)= 49x²-49x-x²-7x +49 -7x =48x²-63x +49

Szczegółowe wyjaśnienie: